Calcium Channel Antagonist Toxicity - Elaine Fielder; Daniel Lemke; Cara Doughty (Association of American Medical Colleges, 2014)
Abstract Introduction This simulation case was designed to teach emergency medicine physicians, pediatricians, and other health care providers about the clinical presentation, stabilization, and medical management of the patient with suspected or proven toxic ingestion of calcium channel antagonists (CCAs). Simulation was chosen because it allows for team-based practice and fine-tuning of a systematic approach to acutely ill patients in a safe learning environment. The overall goal was enhanced recognition and management of pediatric patients with high-acuity, low-frequency toxicologic emergencies. Methods This case centers on an adolescent patient with altered mental status and suspected toxic ingestion. The case requires use of Laerdal SimMan 3G and its associated software and program files. The scenario was conducted in a resuscitation room equipped with standard pediatric resuscitation equipment, including airway equipment, monitors and defibrillators, IV access, and standard resuscitation drugs. The scenario was designed to take 10-15 minutes to complete, with 30 minutes immediately following to debrief. Results Pilot testing was completed at the Texas Children's Hospital Simulation Center on July 21, 2012. A total of 12 pediatric emergency medicine fellows and four pediatric emergency medicine nurses participated in the scenario, divided into four groups. This was a nongraded interactive learning experience. At the end of the simulation day, all participants filled out a course evaluation that included specific feedback about scenarios, content, and instructors. Based on this feedback, scenarios were modified for future use. Discussion Our workshop included only pediatric emergency medicine fellows and nurses and therefore has not been evaluated with other learner groups. We did not include a didactic session with the scenario but feel this may have been helpful to the participants' overall learning experience.